Etanercept - A culprit agent in acute pancreatitis? - Ferry Gunawan; Beenish Fayyaz; Tania Octaria Mihardja (Greater Baltimore Medical Center, 2019)
Drugs are responsible for 3%-5% of acute pancreatitis cases. There are a lot of medications that are known to cause acute pancreatitis, however only one case has been reported so far on Etanercept. This is a case about 62-year old female with history of Rheumatoid arthritis (RA) was started on Etanercept to control her severe RA symptoms. Three weeks later, she presented with abdominal pain, nausea, vomiting and found to have acute pancreatitis based on clinical symptoms and elevated pancreatic enzymes. A thorough workup for the cause of pancreatitis was done and all were unrevealing. There was no history of alcohol use, abdominal trauma or any gastroenterology procedures. Ultrasound and CT abdomen ruled out hepatobiliary abnormalities. Lipid profile and electrolytes including calcium were also found to be normal. As all the workup was unremarkable, it was thought that drug-induced acute pancreatitis was likely the case. Etanercept was the only medication that was started recently, which made it the likely culprit and therefore it was stopped. Patient continued to improve and was discharged after medical stabilization. Her rheumatologist started her on Abatacept and she has remained symptom-free since then. Our case is interesting as it is the second case of etanercept induced acute pancreatitis. Furthermore, recent animal trials have demonstrated that etanercept potentially has a protective and/or therapeutic role in acute pancreatitis. However, no human studies regarding this topic have been performed. Due to limited data, a clear explanation behind these paradoxical actions of etanercept is still lacking.